Thresholds of Body Composition Changes Associated with Survival During Androgen Deprivation Therapy in Prostate Cancer - Pin-Chi Chen; Pai-Kai Chiang; Jhen-Bin Lin; Wei-Kung Tsai; Wan-Chun Lin; Ya-Ting Jan; Kun-Pin Wu; Jie Lee (European Urology Open Science)
Background and objective: Androgen deprivation therapy (ADT) is associated with reduced muscle and increased fat mass in patients with prostate cancer. However, the threshold for body composition changes associated with survival during ADT remains unclear. This study aimed to identify body composition change thresholds for all-cause mortality during ADT. Methods: We enrolled 538 patients with prostate cancer (332 and 206 in the derivation and external validation cohorts, respectively) who underwent radiotherapy and ADT at two tertiary centers. Computed tomography (CT) images at baseline and 6 mo after ADT initiation were retrieved for an analysis. Skeletal muscle index (SMI), subcutaneous adipose tissue index (SATI), and visceral adipose tissue index (VATI) were measured using CT at the L3 vertebral level. Optimal thresholds for body composition changes were determined using the Shapley Additive Explanations (SHAP) method and validated using a Cox proportional hazard model. Key findings and limitations: Changes in SMI, SATI, and VATI were the three most important features for predicting all-cause mortality. SMI change was inversely associated with the all-cause mortality risk, and changes in the SATI and VATI showed a U-shaped relationship with the all-cause mortality risk. SMI loss (≥4.0%), SATI gain (≥15.0%), and VATI gain (≥12.0%) were independently associated with an increased all-cause mortality risk (SMI loss: hazard ratio, 6.79, p < 0.001; SATI gain: hazard ratio: 2.95, p = 0.002; VATI gain: hazard ratio: 2.91, p < 0.001). Conclusions and clinical implications: The thresholds determined in this study can help identify patients with considerable body composition changes after 6 mo of ADT and guide interventions to improve body composition. Patient summary: We identified muscle loss and increased adipose tissue thresholds associated with all-cause mortality during androgen deprivation therapy for men with prostate cancer. These thresholds can help guide interventions to improve body composition and potentially improve outcomes.